Predicting Low Birth Weight: A comparison of Anthropometric Measurements taken by Midwives and Community Health Workers in Uganda - Ayesiga, Savino; Abaasa, Catherine; Ayebare, David; Maina, Gakenia Wamuyu (Research square, 2019)
Background: In many resource constrained countries, Uganda inclusive, women continue to give birth at home/in the community where there are no weighing scales to measure and record birth weight, and consequently low birth weight remains undetected. Low birth weight, if not urgently detected and attended to reduces chances for growth. This study was to compare newborn anthropometric measurements taken by midwives to those taken by community health workers and to determine cut offs to predict low birth weight in south western Uganda. Methods: A descriptive cross sectional study was conducted between July and September 2017, whereby anthropometric values of 638 newborns born at Mbarara Regional Referral Hospital were measured by two midwives but repeated anthropometric measurements by CHWs were taken only 553 newborns because of loss to follow up. Frequencies, means (standard deviation) were used to describe categorical and continuous demographics of newborns respectively. Pearson correlations were made to test for the associations between main explanatory variables. Specificity, sensitivity, likelihood ratios, diagnostic odds ratios (DOR) and area under the curve (AUC) were used to determine low birth weight at set cut off points of various anthropometric measurements. An independent paired t-test was then conducted to establish whether there was a statistical significant difference between the anthropometric measurements taken by midwives and CHWs. Results: Chest Circumference was the most predictor of low birth weight. Of the 29 (5.2%) low birth weight newborns, chest circumference at a cut off of 30.9 cm was able to predict the highest prevalence of low birth weight as per the anthropometric measurements taken by midwives. Also, anthropometric measurements taken by midwives and those taken by Community Health Workers (CHWs) showed no statistical significant mean differences. Conclusions: Chest circumference is the best predictor of low birth weight in western Uganda. Also, Community Health workers can measure chest circumference with almost the same accuracy like midwives. Keywords: Birth weight, anthropometric predictors, newborns
Keywords: Birth weight; Anthropometric predictors; Newborns